Towards a Global Democratic State: crisis and Constitutions - Seijas Villadangos, Esther (2015)
The economic crisis and the phenomenon of globalization have generated such a   great impact on States that it has also had an effect onConstitutional Law, since the attention has beenturned towards the possibilities of constitutional reforms  and the question about the role the Constitutions should play in this scenery.In this context, the author states that the crisis must be seen as an opportunity to reconfigurate the relations between the State and the citizens. She maintains that because of the crisis, paradoxes have been created and made evident, and in the solution of  those  paradoxes  Constitutional Law and the Constitutions of each State can be of valuable help.